Analisis Manajemen Pembelajaran Anak Usia Dini Berbasis Pendidikan Karakter - Muhammad Ihsan Dacholfany; Trisna Rukhmana; Al Ikhlas; Supriyono Supriyono; Karsim Karsim; Loria Wahyuni (Journal on Education, 2024)
This research discusses the analysis of early childhood learning management based on character education with the aim of gaining an in-depth understanding of the implementation of a holistic approach in the learning process. Qualitative research methods were used with a case study design at early childhood education institutions. The research results show that learning management integrated with character education is successful in creating a learning environment that is conducive to children's development. Teachers actively involve children in learning activities that emphasize moral values ​​such as honesty and responsibility. High children's participation and positive character development are the hallmarks of this approach. The practical implications of this research provide guidance for educators and policy makers in designing early childhood learning strategies that do not only focus on cognitive aspects, but also pay attention to character development.